Multi-disciplinary investigations at PoW Camp 198, Bridgend, S. Wales: site of a mass escape in March 1945. Issue 2 (1st September 2016) - Rees-Hughes, L.; Pringle, J. K.; Russill, N.; Wisniewski, K. D.; Doyle, P.
Abstract: The largest escape of German Prisoner of War (PoW) in WW2 was in March 1945 from Camp 198, situated in Bridgend, South Wales, UK. Since camp closure the site has become derelict, and has not been scientifically investigated. This paper reports on the search to locate the PoW escape tunnel that was dug from Hut 9. This hut remains in remarkable condition, with numerous PoW graffiti still present. Also preserved is a prisoner-constructed false wall in a shower room behind which excavated material was hidden, though the tunnel entrance itself has been concreted over. Near-surface geophysics and ground-based LiDAR were used to locate the tunnel. Mid-frequency GPR surveys were judged optimal, with magnetometry least useful due to the above-ground metal objects. Archaeological excavations discovered the intact tunnel and bed-board shoring. With Allied PoW escape camp attempts well documented, this investigation provides valuable insight into German escape efforts. Abstract :